Charity and Change: Montreal English Protestant Charity Faces the Crisis of Depression - MacLennan, Anne (Urban History Review / Revue d'histoire urbaine, 1987)
The depression of the 1930s forced private and public charities across Canada to adapt to new circumstances. The crisis was particularly acute for the Montreal Council of Social Agencies, a minority English Protestant organization in a city reluctant to accept any responsibility for public services. The Council was forced to assume the burden of relief services for its community. The abrupt and long term disruptions in the operations of the Council caused by the Depression forced it to reevaluate and reassess its role in social services. Consequently, the Montreal Council of Social Agencies tried to compel municipal, provincial and federal governments to play larger roles in welfare work to relieve immediate and future problems. Most importantly, the Montreal Council of Social Agencies was guided through the 1930s by the principles of the Charity Organization Society, which were retained and reinforced rather than weakened by this crisis.